Two Years Profile of Anemia in Systemic Lupus Erythematosus Patients at West Java’s Top Referral Hospital, Indonesia - Stefanie Yuliana Usman; Laniyati Hamijoyo; Anna Tjandrawati (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Anemia is a common clinical manifestation in Systemic Lupus Erythematosus (SLE) patients. Anemia can be caused by an ineffective hematopoietic process or excessive red blood cell destruction. The aim of this study was to classify and characterize anemia in SLE patients.Methods: This study involved 97 outpatients visiting the Rheumatology Clinic of Dr. Hasan Sadikin General Hospital Bandung, from January 2013 to September 2014. Patient data was collected from medical records and study subjects were selected according to the American College of Rheumatology 1997 criteria for SLE, and the characteristic of anemia among outpatients were described according to the World Health Organization criteria.Results: The characteristics among 97 respondents showed 95 (98%) were female; 32 (33%) were 21–30 years old; and 49 (51%) had SLE for 1–5 years. The characteristics and classification of anemia, 57 (59%) had normocytic normochromic, and 33 (34%) had microcytic hypochromic anemia. According to the severity classification, 48 (50 %) had moderate anemia, only 8 (8%) had severe anemia. Four (4%) subjects had anemic conjunctiva, 45 (46%) had fatigue and 48 (50%) had no clinical manifestations of anemic conjunctiva and fatigue.Conclusions: Moderate anemia, normocytic normochromic anemia are the most prevalent among the subjects. Half of the anemic SLE patient has no clinical manifestation of anemic conjunctiva and fatigue.DOI: 10.15850/amj.v4n2.1094